Genetic diversity among bread wheat (Triticum aestivum L.) genotypes as assessed by SSRs - Sharma, Renuka; Kumar, Satish; Singh, Sanjay Kumar; Sharma, Pradeep; Singh, Gyanendra Pratap (Journal of Cereal Research, 2021)
Drought is one among the several climatic factors impeding crop productivity and poses a challenge to global food security. The intensity and frequency of droughts are predicted to increase by 50% to 200% during the 21st century in various geographical regions. Raising drought tolerant wheat genotypes is the eventual means of safeguarding the crop against water stress. However, drought tolerance is a complex trait governed by various genes, each with minor effects. Knowledge about germplasm diversity significantly impacts the crop improvement programs by supplying novel sources of gene combinations. Prior knowledge of genetic diversity and relationships between the elite lines and cultivars are useful for development of new cultivars. It is highly desirable to characterize genetic diversity among wheat germplasm collections to broaden genetic diversity in future wheat breeding programmes